PENGARUH PEMBERIAN KREDIT, SISTEM INFORMASI AKUNTANSI DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KINERJA UMKM (Manajemen & Bisnis Jurnal, 2022)
This study aims to examine the effect of credit providers, accounting information systems and human resource competencies on the performance of MSMEs. In this study, the dependent variable and the independent variable were used, and the data sources in this study used primary and secondary data. This research uses descriptive analysis method, data instrument test, classical assumption test, multiple linear regression analysis and hypothesis testing. This research was conducted on the owners of Dinoyo Ceramic SMEs in Malang City. The sampling technique in this study uses the census method or complete enumeration, that is, if all members of the population become the sample, so the sample in this study is 32 SMEs. Based on the test results, it can be concluded that the provision of credit has an effect on the performance of MSMEs. Accounting Information System has an effect on MSME Performance. And Human Resource Competence has an effect on the performance of MSMEs.